Petrogenesis of the syntectonic Matok Pluton in the Limpopo Belt (South Africa) and its implications of the geodynamic environment - Rapopo, Mafusi (Stellenbosch : Stellenbosch University, 2011)
Thesis (MSc)--Stellenbosch University, 2011.